Differential diagnosis in children with musculoskeletal pain in Emergency Department - Małgorzata Drozd; Adrianna Gorecka; Bartłomiej Zaremba; Violetta Opoka-Winiarska (Kazimierz Wielki University, 2022)
Objective: The study was aimed to analyze the diagnostic approach to a child with a non-traumatic musculoskeletal pain registered in the pediatric Hospital Emergency Department (HED). Since the pandemic COVID-19 affects patient health and the healthcare system, we also evaluated the impact of pandemic on type of musculoskeletal symptoms. Study design: A retrospective cross-sectional study was conducted by statistical analysis of data of patients with non-traumatic musculoskeletal pain registered in HED between January 2018 and December 2020. Data of patients referred and not referred to hospital ward and admitted to HED before and during COVID-19 pandemic have been compared. Results: Majority of patients presented acute, non-trauma related, single-site pain, usually localized in the hip, the knee and the spine. 21,49% of patients were referred to a hospital ward, usually rheumatological, neurological or orthopedic. Final diagnoses in almost ¾ patients belong to the group of musculoskeletal system and connective tissue disorders. During the pandemic significantly less patients with musculoskeletal pain reported to our HED. The duration of symptoms before admission was not significantly longer than in previous years, but the problem in children and the impact of the pandemic on the musculoskeletal system in children is complex. Conclusions: Our study provides detailed information on patterns of pediatric musculoskeletal consultations in HED. A positive history of trauma preceding musculoskeletal pain in a child may only be accidentally related to the final cause. Musculoskeletal pain can be also a symptom of a lot of various systemic conditions, not only diseases of the musculoskeletal system. The still ongoing COVID-19 pandemic may require changes in the organization of the HED. We believe that the presented results can help in organizing and planning care in pediatric HEDs, develop diagnostic algorithms and training for HED staff.